Dynamic and Steady Model Development of Two-Chamber Batch Microbial Fuel Cell (MFC) - Ardiyan Harimawan (Dept. of Chemical Engineering, Diponegoro University, 2021)
As an alternative source of renewable energy that has piqued researchers’ interest, Microbial Fuel Cell’s (MFC) limitation of low power density requires further development. Various factors affect the performance, but performing all will be costly and time-consuming. Through a combination of dynamic and steady-state mathematical model modified from past research, effect of microbe types towards dynamic biofilm formation and stead-state OCV can be observed, followed by steady-state simulation to determine maximum power density and its’ corresponding voltage. Similarity with previous research has been observed, with maximum OCV of 838.93 mV achieved by heterotrophic biomass in 75-100 hours with biofilm thickness of 2.087 x 10-4 m, while generating maximum power density of 2050.12 mW//m2 and voltage of 408.16 mV. Lowest OCV value of 838.76 mV was observed in C. sporogenes in 450-475 hours with a biofilm thickness of 2.079 x 10-4 m, while the lowest value of maximum power density was observed in anaerobic microbial communities at 8.48 mW/m2 with voltage of 90.43 mV. Furthermore, it has been observed that variations with higher and lower results in higher stead-state OCV in the shortest amount of time, while increasing power density and its’ corresponding voltage. @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536869121 1107305727 33554432 0 415 0;@font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-469750017 -1073732485 9 0 511 0;p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman",serif; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-US;.MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; font-family:"Calibri",sans-serif; mso-ascii-font-family:Calibri; mso-fareast-font-family:Calibri; mso-hansi-font-family:Calibri; mso-ansi-language:IN; mso-fareast-language:IN;div.WordSection1 page:WordSection1;